1995
DOI: 10.1074/jbc.270.50.29656
|View full text |Cite
|
Sign up to set email alerts
|

Release of Gelatinase A (Matrix Metalloproteinase 2) Induced by Photolysis of Caged Phosphatidic Acid in HT 1080 Metastatic Fibrosarcoma Cells

Abstract: Phosphatidic acid (PA) is a putative novel messenger in signal transduction and membrane traffic. We have synthesized a photolyzable derivative of PA, termed caged PA (cPA), which may be utilized as a new tool in studies of PA-mediated cellular events. 1-(2-Nitrophenyl)diazoethane, synthesized from 2-nitroacetophenone, was reacted with dipalmitoyl-PA to yield a 1-(2-nitrophenyl)ethyl ester of PA. Photolysis of the compound by ultraviolet light resulted in the formation of phosphatidic acid. The structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Thus, we designed a veiled, MMP-sensitive nanosensor by conjugating the photolabile small molecule 1-(4,5-dimethoxy-2-nitrophenyl) diazoethane (DMNPE) to protease cleavable substrates (Figure ). DMNPE reacts with acidic groups , and, by coupling it to an MMP substrate sequence containing free carboxylic acid side chains, serves as a removable barrier to block enzymatic cleavage. Furthermore, we hypothesized, based on previous studies, that DMNPE should be located within a few amino acids from the putative cleavage site in order to effectively block protease activity by steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we designed a veiled, MMP-sensitive nanosensor by conjugating the photolabile small molecule 1-(4,5-dimethoxy-2-nitrophenyl) diazoethane (DMNPE) to protease cleavable substrates (Figure ). DMNPE reacts with acidic groups , and, by coupling it to an MMP substrate sequence containing free carboxylic acid side chains, serves as a removable barrier to block enzymatic cleavage. Furthermore, we hypothesized, based on previous studies, that DMNPE should be located within a few amino acids from the putative cleavage site in order to effectively block protease activity by steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
“…Our results show a significant dose-dependent expression of PRL-3 in response to exogenous laminin (Figure 3A). In previous studies, we have shown that laminin signaling involves activation of phospholipase D (PLD) enzymes [25,26]. We repeated the experiments in the presence of primary and secondary alcohol, known modulators of PLD signal transduction.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to participating in cell survival pathways, PLD is thought to contribute to cancer metastasis via multiple mechanisms, including cytoskeletal rearrangement and cell migration 31 . Recent reports suggest PLD may also contribute to metastasis through the induction of matrix metalloproteinase (MMP) secretion and extracellular matrix degradation 4145 . PLD has also been suggested to have pro-angiogenic properties via interactions with sphingosine kinase-1 and sphingosine-1-phosphate (S1P) 46 .…”
Section: Discussionmentioning
confidence: 99%